ENHANCING CITIZENSHIP EDUCATION AS A TOOL AGAINST INSECURITY CHALLENGES IN NIGERIA - Undie, Joseph; Aboh, Fidelis; Omang, Cornelius (African Journal of Social and Behavioural Sciences, 2025)
This paper advocates for enhancing citizenship education, which has the potential to reform, resocialize, and resensitize youths to the need to abandon their destructive, retaliatory, and violent activities that threaten Nigeria's statehood. It aims to foster democratic values and civic responsibilities through citizenship education. The question of insecurity challenges in Nigeria is becoming worrisome as vicious groups are now mushrooming day by day in our society, posing an unimaginable vicious threat that rocks the peaceful existence of members of the society. Given the state we have found ourselves in, we urgently need to enhance citizenship education as a tool against these insecurity challenges. This is because many Nigerians are bitter, always in a disposition to attack the state and its people due to their frustration, anger, and disbelief against the government and statehood. Given the efficacy of citizenship education, as surveyed in literature review, it is a tool in fostering ideal civic attitude and competence, it is therefore pertinent for the subject to be enhanced upon to produce citizens with the right psyche, consciousness, disposition, and mentality that will not only uphold the ideals of democracy, promote human rights and the principle of equality, but also appreciate the gift of diversity and participate actively towards building a society that is safe, peaceful and prosperous. Therefore, this paper dealt with the goals of citizenship education, empirical evidence on the effect of citizenship education, the challenges of teaching citizenship education, the way forward to enhance citizenship education, and conclusion-bearing recommendations.